2014
DOI: 10.14419/ijbas.v4i1.2655
|View full text |Cite
|
Sign up to set email alerts
|

Primary bone tumours in Kashmir valley a retrospective histopathological study

Abstract: The present study was carried out in the postgraduate department of Pathology at Government Medical College, Srinagar, India, to study the histopathological pattern of primary bone tumors in Kashmir valley over a period of 15 years. During this study, 373 histologically proven primary bone tumors were analyzed. Out of these, 298 were benign (79.89%) and 75 were malignant (20.10%). Peak incidence was in the second and third decade of life with male predominance. Among the malignant tumors, the highest incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
3
0
0
Order By: Relevance
“…3 Clinical features of bone tumours are mainly non-specific or not recognised, and usually not detected in the initial stages 11 , so experience in diagnostic orthopaedic pathology is also needed in maintaining the high standard of histological reporting. 12 In present study we evaluate 68 cases of neoplastic lesions of bone, we observed that these lesions are more common in younger persons between 20 -40 years of age, as observed by other studies 13 and the male (60.3%) were found affected more than the females, this was also the observation of other researchers mentioned in the literature. 1,7,10,14 We detect majority of benign (63.2%) cases in our study, which was in consistent with the findings of other studies 10,13,15 some studies showed a very high (84%) frequency of benign tumors 16 , these differences may be due to differences in sample size and selection criteria.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…3 Clinical features of bone tumours are mainly non-specific or not recognised, and usually not detected in the initial stages 11 , so experience in diagnostic orthopaedic pathology is also needed in maintaining the high standard of histological reporting. 12 In present study we evaluate 68 cases of neoplastic lesions of bone, we observed that these lesions are more common in younger persons between 20 -40 years of age, as observed by other studies 13 and the male (60.3%) were found affected more than the females, this was also the observation of other researchers mentioned in the literature. 1,7,10,14 We detect majority of benign (63.2%) cases in our study, which was in consistent with the findings of other studies 10,13,15 some studies showed a very high (84%) frequency of benign tumors 16 , these differences may be due to differences in sample size and selection criteria.…”
Section: Discussionsupporting
confidence: 84%
“…12 In present study we evaluate 68 cases of neoplastic lesions of bone, we observed that these lesions are more common in younger persons between 20 -40 years of age, as observed by other studies 13 and the male (60.3%) were found affected more than the females, this was also the observation of other researchers mentioned in the literature. 1,7,10,14 We detect majority of benign (63.2%) cases in our study, which was in consistent with the findings of other studies 10,13,15 some studies showed a very high (84%) frequency of benign tumors 16 , these differences may be due to differences in sample size and selection criteria. Among 43 benign tumors, we diagnose majority (25.6%) of cases as osteochondroma followed by 21 % cases of Benign Giant Cell Tumor.…”
Section: Discussionsupporting
confidence: 84%
“…[7] Benign lesions were more common than malignant lesions. [8][9][10][11][12][13] Neoplastic lesions were found to be more common than non-neoplastic lesions which is in conformity with studies done by Settakom et al [14] Chronic osteomyelitis was most common non-neoplastic condition affecting 7 patients (38.9%). Other non-neoplastic conditions were tubercular osteomyelitis and ABC.…”
Section: Discussionsupporting
confidence: 77%